INTEGRASI PROGRAM FULL DAY SCHOOL DAN HABITUASI KARAKTER ISLAMI PADA SMP ISLAM TERPADU KOTA LANGSA - Mahyiddin Mahyiddin; Razali Mahmud; Muhammad Affan (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Internalization and habituation of Islamic character in Integrated Islamic schools are realized through the full-day school program. Through character education students are expected to be able to independently improve and use their knowledge, study and instil the values of character so that it is manifested in daily behaviour. The purpose of this study was to determine the flagship full-day school program from SMPIT in Langsa City. Data collection techniques carried out by interview and documentation. The results showed that there were differences in the curriculum used by schools and the educational background of teachers. Muhammadiyah SMPIT combines the National curriculum, dayah education and kemuhammdiyahan and has teachers from foreign and domestic graduates, while SMP Tadzkia integrates the National curriculum with the JSIT curriculum and domestic graduate teachers